Petiole rot caused by Fusarium monoliforme, a new disease or Areca palm - Dal Bello, G.M.; Lori, G.A. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
Symptoms of a previously undescribed disease were observed on greenhouse-planted Areca palms (Chrysalidocarpus lutescens), grown in La Plata (Buenos Aires, Argentina). Lower young petioles were rotted with the decay extending to the entire leaves. White mycelium was observed on diseased petioles from which a Fusarium sp. was recovered. Based on morphological and cultural criteria all isolates were identified as F. moniliforme. Pathogenicity was demonstrated on Areca plants inoculated with the fungus. F. moniliforme was reisolated from the inoculated palms to complete Koch's postulates.